Rozpacz jako życie w śmierci w myśli Sørena Kierkegaarda - Kaftański, Wojciech (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2012)
The author of this article outlines the background of the origins of The Sickness Unto Death and its main theme: despair. Consequently, he presents despair as built upon Kierkegaard’s concept of the human self. Despair characterizes the condition of the human self. Moreover, it depicts the process of disintegration of the human self and reflects the condition of a bourgeois mentality in society. The essay presents despair as the spiritual death of a single individual both for him/herself and for society, which results in the subsequent disintegration of society. Despair is a sickness that produces a life which is unfulfilled, inadequate and untrue as well as devoid of spirituality, intimacy and reflection.